Game-related statistics which discriminate between winning and losing teams in Asian and European men`s basketball championships - Madarame, H. (Asian Journal of Sports Medicine, 2017)
Background: Basketball is one of the most popular sports in the world. However, men`s national teams of Asian countries have not performed well at world-level competitions such as Olympic and world cup games. Clarifying the feature of Asian basketball games would be some help to improve the competitiveness of Asian teams.